Implementation of Fazlur Rahman and Syed Naquib al-Attas' Educational Concepts in Islamic Full-day Schools - Sudirman, Sudirman; Minarti, Sri; Ramadani, Laili (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study aims to analyze the implementation of Fazlur Rahman and Syed Naquib Al-Attas' educational concepts in full-day schools in Indonesia. The institutions studied implement an integrated curriculum that combines formal madrasah education with pesantren-style learning, in order to meet the needs of parents who want their children to receive Islamic education without having to live in a full-day schools. The research focuses on the integration of muhadatsah, muhadharah, tahsin-tahfidz, imla’, nahwu-sharaf, and mahfudzoh programs with the Ministry of Religious Affairs curriculum. The research used qualitative methods with a case study approach, through participatory observation, semi-structured interviews with eight key informants (head of the madrasah, deputy head of curriculum, Islamic Education teachers, tahfidz teachers, and students), and documentation studies. Data analysis was conducted inductively using the Miles and Huberman model, through the stages of reduction, presentation, and conclusion drawing, accompanied by triangulation of sources and methods to ensure the validity of the findings. The results of the study indicate that educational practices in these schools reflect the application of the principles of Quranic knowledge and moral integration according to Fazlur Rahman and the concepts of adab and spirituality according to Syed Naquib Al-Attas, which combine to form a modern Islamic education model that harmoniously integrates rationality, morality, and spirituality into a full-day school system. These findings contribute to the development of a holistic, contextual, and adaptive Islamic education paradigm that meets the needs of modern urban communities.